Research of the mineral composition and determination of some quality indicators of the flowers and herbs of snapdragons (Antirrhinum majus L.) - Illyna, Sophya; Zhuravel, Iryna (Annals of Mechnikov's Institute, 2023)
Introduction. Plants serve as a source of biologically active substances used for the prevention and treatment of various diseases. One such species is snapdragons (Antirrhinum majus L.) – an herbaceous plant belonging to the Plantain family (Plantaginaceae). This decorative plant is widely utilized in gardening due to its vibrant color and distinctive flower shape. In nature, it is distributed from central France to northeastern Spain and the Balearic Islands. In Ukraine, snapdragons are cultivated, providing a raw material base. Historically, the plant has found application in the traditional medicine of various countries worldwide. Infusions of the flowers were used to alleviate headaches, treat edema and dyspnea, while externally, they were applied to heal ulcers and boils. Tea made from the leaves was prepared and used to address liver and kidney ailments, meteorism, and jaundice. In the modern world, the pharmacological activity of snapdragon flowers has been investigated by foreign scientists. Researchers from the Malaysian Scientific University studied the wound-healing, anti-inflammatory, and antimicrobial activity of the raw material. Additionally, at Inha University (Korea), the inhibitory effect of the plant's flower extract on the growth of certain cancer cell types and the reduction of their metastatic properties was examined. The determined activities may be associated with the mineral composition. In previous studies conducted by scientists from the Polish University West Pomeranian University of Technology, the presence of elements such as potassium, calcium, phosphorus, sodium, magnesium, and iron was demonstrated in the raw material of snapdragon flowers. Potassium is involved in regulating the function of the heart, nervous system, skeletal, and smooth muscles. Calcium ions are necessary for the formation of bone tissue, transmission of nerve impulses, muscle contraction, regulation of heart function, and blood clotting. Phosphorus is essential for the formation and development of teeth and bones, the functioning of kidneys, nerves, muscles, and the heart. Sodium participates in muscle contraction, transmission of nerve impulses, gastric juice formation; regulates acid-base balance, tissue hydrophilicity, blood, lymph, and kidney functions; activates enzymes of the pancreas and salivary glands. Magnesium is important for bone formation, regulation of nerve and muscle function, protein, lipid, carbohydrate, and energy metabolism, DNA and RNA structuring, and strengthens tooth enamel. Iron is necessary for the synthesis of hemoglobin, myoglobin, catalase, and peroxidase, playing a significant role in direct and indirect oxidative processes and ensuring the normal functioning of the immune system. For the utilization of snapdragon flowers and herb in evidence-based medicine, it is necessary to standardize this raw material. The State Pharmacopoeia of Ukraine regulates criteria for the standardization of medicinal plant raw materials, including heavy metal content, mass loss upon drying, and total ash content. Therefore, determining these indicators is relevant and necessary. Materials and methods. The objects of the study were the grass and flowers of snapdragons (Antirrhinum majus L.) of the varieties Overture and Snappy. The raw material was harvested during the flowering phase of the plants in August 2023 in the Kharkiv region, Ukraine. For the analysis of the mineral element content, an atomic emission spectrometric method was employed. This method is based on the vaporization of samples from craters of graphite electrodes in an alternating current arc and the registration of the obtained spectra on a photosensitive plate PFS-02. The DFS-8 spectrometer was used, and the alternating current arc was generated using the IBC-28 generator. Spectral graphite electrodes labeled "OSC" were employed. Graduation samples and prepared specimens were placed in the craters of the lower electrodes (depth 4 mm, diameter 4.5 mm) and upper electrodes (depth 5 mm, diameter 1.9 mm). The measurement conditions were set as follows: the current of the alternating current arc - 16 A; ignition phase - 60°C, frequency of ignition pulses - 100 discharges per second, analytical gap - 2 mm, slit width - 0.015 mm, exposure - 60 s. Spectra were photographed in the range of 240-350 nm. For the investigated chemical elements, the results of the analyses were calculated based on the difference in emission line darkening and background. The quantitative content of the chemical element (%) relative to the base was determined using a calibration graph. The results were processed using mathematical statistical methods. The loss in mass upon drying and the content of total ash in the raw material were determined by the gravimetric method according to the State Pharmacopoeia of Ukraine. Results and discussion. Nineteen mineral elements were experimentally identified and their content determined in the grass and flowers of two investigated varieties of snapdragon. Among the identified elements, five belong to macroelements (potassium, sodium, calcium, phosphorus, magnesium), eleven to microelements (iron, manganese, zinc, copper, silicon, strontium, molybdenum, nickel, cobalt, aluminum, arsenic), and three to toxic elements (lead, cadmium, mercury). Among the identified mineral elements, essential elements were highlighted, meaning those vital for the normal functioning of the immune and other systems in humans. All the determined 5 macroelements are essential (potassium, sodium, calcium, phosphorus, magnesium). Additionally, 7 microelements were classified as essential (silicon, iron, manganese, zinc, copper, molybdenum, cobalt), and 2 were considered conditionally essential microelements (nickel, arsenic). Comparing the content of essential elements in the raw material of snapdragon, the highest values were found in the grass of the Overture variety, while the lowest were in the flowers of the same variety. Different types of raw materials from the Snappy variety showed almost no difference in the content of these elements. The analysis of the total content of mineral elements in the investigated raw material revealed a slightly higher content in the grass of the Overture variety compared to other types of raw material (4198.50 ± 125.95 mg/100 g). The lowest content of the examined elements was recorded in the flowers of the same variety (3765.60 ± 112.97 mg/100 g). Although the list of available microelements was broader, in terms of quantitative content, macroelements predominated in the investigated raw material. Among the macroelements, potassium, calcium, magnesium, and phosphorus predominated in all types of raw materials. The Snappy variety grass accumulated a slightly higher amount of sodium. The flowers of the Overture variety had a lower potassium content compared to the grass, while in the flowers and grass of the Snappy variety, the difference in values was not significant. The calcium and phosphorus content in the flowers of both varieties was approximately at the same level and lower than in the grass. The magnesium content was higher in the grass of the Overture variety. Silicon, strontium, iron, and aluminum were next in abundance. The content of these microelements in the grass of both varieties had similar values. The analysis of flowers showed that magnesium, as well as strontium, iron, and aluminum, predominated in the raw material of the Snappy variety, while in the flowers of the Overture variety, a higher silicon content was observed. Manganese, zinc, copper, molybdenum, nickel, lead, and cadmium were accumulated in small amounts and did not significantly differ in content in all types of snapdragon raw materials. The total content of macroelements was higher in the grass of the Overture variety (3732.00 ± 111.96 mg/100 g). The grass and flowers of the Snappy variety had similar values (3425.00 ± 102.75 mg/100 g and 3416.00 ± 102.48 mg/100 g, respectively) and occupied the second position in terms of the quantity of macroelements. The least amount was determined in the flowers of the Overture variety (3305.00 ± 99.15 mg/100 g). The content of microelements in the investigated raw material of snapdragons did not significantly differ. The smallest total content was observed in the grass of the Snappy variety (413.51 ± 12.40 mg/100 g). The content of toxic elements, such as cadmium, cobalt, mercury, lead, and arsenic, did not exceed the permissible limits set by the State Pharmacopoeia of Ukraine. The ash content and values of loss on drying were determined in the raw material of 7 series. The ash content in the grass of snapdragon varieties Snappy and Overture was 8.46 ± 0.25 % and 10.14 ± 0.30 %, respectively. In the flowers of both examined varieties, this indicator hardly differed (8.60 ± 0.26 % for Overture and 8.70 ± 0.26 % for Snappy). The highest ash content was determined in the grass of Snapdragon Overture, and the lowest was in the grass of Snappy. The loss in mass during drying was 12.28 ± 0.33 % in the grass of Snapdragon Snappy and 12.23 ± 0.32 % in the grass of Overture. In the flowers of Overture, the loss in mass during drying was 12.35 ± 0.36 %, and for Snappy, it was slightly higher at 12.57 ± 0.39 %. Conclusions. The study investigated the mineral composition of Snapdragon Snappy grass and flowers, determining the loss in mass during drying and the ash content in this raw material. Potassium, calcium, magnesium, phosphorus, sodium, and silicon predominated in both grass and flowers. The content of other elements was lower. The results obtained showed that the raw material of the studied varieties did not significantly differ in composition and content of mineral elements, total ash, and loss of mass during drying. The content of toxic substances did not exceed the permissible limits. The obtained experimental data will be used for the standardization of garden snapdragon plant material and the development of medicinal products based on it. Keywords: Antirrhinum majus L., Snapdragon, mineral composition, essential elements